2014
DOI: 10.3844/ajidsp.2014.64.67
|View full text |Cite
|
Sign up to set email alerts
|

Detectable Anti-Dengue Virus Igm Antibodies Among Healthy Individuals in Ogbomoso, Oyo State, Nigeria

Abstract: Dengue fever is a zoonosis maintained in nature by mosquitoes transmitting virus between non-human primate species, most of which develop clinically in apparent infection. It has been found to be endemic in Africa and beyond. A survey for Dengue virus IgM antibody was carried out in Ogbomoso (urban and rural areas) using Enzyme Linked Immunosorbent Assay (WKEA Med Supplies Corp, Dengue fever virus ELISA Kit (China),) to determine the seroprevalence and true incidence of dengue virus in Ogbomoso. A total of 186… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 12 publications
(8 reference statements)
8
20
3
Order By: Relevance
“…However, this observation contrasts that of Oladipo et al [18] who reported a higher prevalence in males than females. The differences in prevalence rates between the genders could be attributed to differences in sample size in the different studies.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…However, this observation contrasts that of Oladipo et al [18] who reported a higher prevalence in males than females. The differences in prevalence rates between the genders could be attributed to differences in sample size in the different studies.…”
Section: Discussioncontrasting
confidence: 56%
“…The higher prevalence of dengue NS1 in males than females reported in this study is in disagreement with Dawurung et al [16] who reported higher prevalence of dengue NS1 in females than males in Jos, Nigeria.The age bracket 1-14 years recorded the highest prevalence rate (76.9%) for DENV IgM antibodies. This result, although higher than the 28.6% reported by Oladipo et al [18] and 35% by Garg et al [24], tallies with their observation on the age bracket that recorded the highest prevalence rates. The findings of this study also agrees with the reports of Shah et al [25] and Anderson et al [26]who also observed a higher prevalence of dengue virus among age group 1-15 years.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…A prevalence of 30.8% was reported by Faneye et al [12], 17.7% by Srinivas et al [13], 17.2% in Ogbomoso by Oladipo etbal. [14] and 0.6% reported by Baba et al [15]. The results of these studies emphasize the importance of surveying dengue fever virus.…”
Section: Introductionmentioning
confidence: 52%
“…The 51.9% prevalence obtained in this study is higher than the report of previous studies in Nigeria. A prevalence of 30.8% was reported by Faneye et al [12], 17.7% by Srinivas et al [13], 17.2% in Ogbomoso by Oladipo et al [14] and 0.6% reported by Baba et al [15].…”
Section: Discussionmentioning
confidence: 98%